The influence of steel 35 wire EDM parameters on the surface roughness and morphology / Alexey A. Fedorov, Alexander V. Linovsky and Anatoliy P. Morgunov - Alexey A., Fedorov; Alexander V., Linovsky; Anatoliy P., Morgunov (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The electrical discharge machining (EDM) is a non-traditional machining method that has been widely used in various industries recently. The two important EDM performance measures are the surface roughness and the surface morphology. The research results of the influence of steel 35 wire EDM parameters, particularly the number of cuts on the surface roughness and the surface morphology are presented. Using the methods of atomic force microscopy, scanning electronic microscopy and profilometry, it is shown that the roughness and morphology of the machined surfaces differs much from the theoretical one, and has some peculiar characteristics. The reasons of the difference between practical results and theory are also described. The main are suggested to be the fast front spreading of a gas bubble, turbulent eddies formed by the flow of the pumped liquid. Besides, a crater with a different structure is found and an attempt to explain its nature is made.